Maintenance planning and scheduling streamline your organization for a lean environment - Kister, Timothy C.
This is a hands-on reference guide for the maintenance or reliability engineer and plant manager. As the third volume in the Life Cycle Engineering series, this book takes the guiding principles of Lean Manufacturing and Maintenance and applies these concepts to everyday planning and scheduling tasks allowing engineers to keep their equipment running smoothly, while decreasing downtime. The authors offer invaluable advice on the effective use of work orders and schedules and how they fit into the overall maintenance plan. There are not many books out there on planning and scheduling, that go beyond the theory and show the engineer, in a hands-on way, how to use planning and scheduling techniques to improve performance, cut costs, and extend the life of their plant machinery. * The only book that takes a direct look at streamlining planning and scheduling for a Lean Manufacturing Environment * This book shows the engineer how to create and stick to effective schedules * Gives examples and templates in the back of the book for use in day-to-day scheduling and calculations.